Oral Vaccination Reduces the Effects of Lawsonia intracellularis Challenge on the Swine Small and Large Intestine Microbiome - Leite, Fernando L.; Winfield, Brittanie; Miller, Elizabeth A.; Weber, Bonnie P.; Johnson, Timothy J.; Sylvia, Fred; Vasquez, Erika; Vannucci, Fabio; Beckler, Dana; Isaacson, Richard E. (Frontiers in Veterinary Science, 2021)
Porcine proliferative enteropathy remains one of the most prevalent diseases in swine herds worldwide. This disease is caused by Lawsonia intracellularis, an intracellular bacterial pathogen that primarily colonizes the ileum. In this study we evaluated changes to the microbiome of the ileal mucosa, ileal digesta, cecal digesta and feces subsequent to challenge with L. intracellularis and to an oral live vaccine against L. intracellularis. Given that gut homogenates have been used since 1931 to study this disease, we also characterized the microbial composition of a gut homogenate from swine infected with L. intracellularis that was used as challenge material. The L. intracellularis challenge led to a dysbiosis of the microbiome of both the small and large intestine marked by an increase of pathobionts including Collinsella, Campylobacter, Chlamydia and Fusobacterium. This microbiome response could play a role in favoring L. intracellularis colonization and disease as well as potentially predisposing to other diseases. Vaccination altered both small and large intestine microbiome community structure and led to a significant 3.03 log10 reduction in the amount of L. intracellularis shed by the challenged pigs. Vaccination also led to a significant decrease in the abundance of Collinsella, Fusobacterium and Campylobacter among other microbial changes compared to non-vaccinated and challenged animals. These results indicate that L. intracellularis infection is associated with broad changes to microbiome composition in both the large and small intestine, many of which can be mitigated by vaccination.